Methodological progress in the study of self-regulated learning enables theory advancement. (April 2021) - Reimann, Peter
Abstract: The collection of papers in this special issue demonstrates the level of methodological sophistication that has become characteristic of contemporary research on self-regulated learning. In this commentary I develop the argument that these methods can lead us not only to improved theoretical models but also to a new type of theory for SRL. In particular, multimodal and temporal methods provide us with an extended epistemic space for SRL research, a move from theories we could describe as 'event-oriented' toward those we might want to call 'structure-oriented'. First, however, I take stock of the range of methods employed in the contributions to this issue.